Association of Plasma Ghrelin with Body Mass Index and Gastric Emptying Time in Patients with Chronic Gastritis - Saleem Ullah Zaffar, Talha Bin Ayub, Bushra Mohyuddin, Abdul Basit Zubair, Naveeda Manzoor, Muhammad Adnan Sadiq (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Ghrelin, a stomach-derived orexigenic peptide, may link gastric mucosal pathology,body mass index (BMI) and gastric motility in chronic gastritis. The present study aimed to investigate the association of fasting plasma